Why Would Phylogeneticists Ignore Computerized Sequence Alignment? - David A. Morrison (2009)
In phylogenetic analyses, multiple sequence align ment often seems to be the poor cousin to tree build ing. It has long been recognized that both primary homology assessment (alignment) and secondary ho mology assessment (tree building) can have important effects on phylogenetic analyses (Morrison and Ellis 1997), and this has been repeatedly demonstrated for both empirical and simulated data (see references cited by Morrison 2008; also Wong et al. 2008). However, most theoretical contributions to phylogenetic analysis continue to involve tree building alone. Indeed, even most review articles continue to treat alignment as being about automated bioinformatics procedures (Wallace et al. 2005; Edgar and Batzoglou 2006; Kumar and Filipski 2007; Notredame 2007) rather than about phy logenetics (Morrison 2006; Phillips 2006). This suggests the possibility that there have been no (or few) theoretical contributions to multiple sequence alignment that practitioners considered to be useful in phylogenetics. In other words, most phylogeneticists are prepared to do tree building in a fully computerized manner but not (yet) alignment. Here, I test this hypoth esis by reviewing the current practices for multiple se quence alignment in published phylogenetic analyses, particularly with respect to differences between disci plines in the way that phylogenetic analyses are used. I also provide suggestions as to why phylogeneticists are apparently dissatisfied with computerized sequence alignment and how we might deal with it. My inten tion is to highlight why phylogeneticists are dissatisfied with similarity-based alignment procedures and what specifically they are doing about it in practice. I con clude that there is currently no bioinformatics approach that is acceptable for phylogeneticists and that there is thus a gaping hole that needs to be filled.